Cotton-Based Flame-Retardant Textiles: A Review - Md. Shahidul Islam; Theo. G. M. van de Ven (BioResources, 2021)
Biodegradable textiles made from cellulose, the most abundant biopolymer, have gained attention from researchers, due to the ease with which cellulose can be chemically modified to introduce multifunctional groups, and because of its renewable and biodegradable nature. One of the most attractive features required for civilian and military applications of textiles is flame-retardancy. This review focuses on various methods employed for the fabrication of cellulose-based flame-retardant cotton textiles along with their developed flame-retardant properties over the last few years. The most common method is to merge N, S, P, and Si-based polymeric, non-polymeric, polymeric/non-polymeric hybrids, inorganic, and organic/inorganic hybrids with cellulose to fabricate flame-retardant cotton textiles. In these studies, cellulose was chemically bonded with the flame-retardants or in some cases, cotton textiles were coated by flame-retardants. The flame-retardant properties of the cotton textiles were investigated and determined by various methods, including the limiting oxygen index (LOI), the vertical flame test, thermal gravimetric analysis (TGA), and by cone calorimetry. This review demonstrates the potential of cellulose-based flame-retardant textiles for various applications.